A self-healing nanocomposite coating with antibacterial, biocompatibility and self-cleaning properties. (August 2021) - Zhu, Yanxi; Zhang, Jinling; Quan, Yanchun; Wei, Li; Zang, Lanlan; Wang, Zhiqiang; Wang, Long; Wang, Lijuan; Che, Fengyuan
Graphical abstract: Highlights: Ag-bPEI/PAA@TiO2 were successfully integrated into bPEI/PAA substrate to realize coating's multifunction. Ag-bPEI/PAA@TiO2 -bPEI/PAA nanocomposite coating had good biocompatibility, antibacterial and self-cleaning property. Ag-bPEI/PAA@TiO2 -bPEI/PAA nanocomposite coating could heal structure damages and restore its original function. Abstract: The functional nanocomposite coatings are easily lose their function with structure damages caused by external forces during their working, which severely restrict their further applications in biomedical. Thus, designing a multifunction nanocomposite coating capable of healing structure damages and maintaining its functions is urgently desired. Here, based on the excellent heterogeneous self-healing property between the poly(ethyleneimine)/poly(acrylic acid) (bPEI/PAA) polyelectrolyte substrate and the shell layer (Ag-bPEI/PAA) of the Ag-bPEI/PAA@TiO2, Ag-bPEI/PAA@TiO2 were integrated into bPEI/PAA substrate to realize coating's multifunction and to inhibit the nanoparticles fall off from the substrate; through the excellent autologous self-healing property of the bPEI/PAA polyelectrolyte, the Ag-bPEI/PAA@TiO2 -bPEI/PAA nanocomposite coating could heal structure damages quickly, reattach the exfoliated nanoparticles to the substrate, restore its original function, thus improve its function stability. The research results showed that the Ag-bPEI/PAA@TiO2 -bPEI/PAA coating not only had good biocompatibility, antibacterial and self-cleaning property, but also had excellent self-healing property and capable of healing structure damages and maintaining stable function. It could be used as an ideal nanocomposite coating for biomedical which needed stable function.